Physical demands of women`s rugby sevens matches: Female athletes in motion (FAiM) study - Vescovi, J. D.; Goodale, T. (International Journal of Sports Medicine, 2015)
his cross-sectional study characterized the locomotor, heart rate and metabolic power characteristics of women`s rugby sevens matches. 4 Canadian teams were monitored during the USA Rugby Sevens event using global positioning system technology with players classified as International (n=16) or Developmental (n=13). Dependent variables were compared between these 2 groups using an ANOVA with duration played as a covariate. International players covered greater distances (1 468±88 m) than Developmental (1 252±135 m); mostly from more high-intensity (224±55 m vs. 131±44 m) and sprint distances (128±67 m vs. 57±44 m). International players also had more distance in high (264±36 m vs. 210±54 m), elevated (118±17 m vs. 76±20 m) and maximal (69±17 m vs. 30 ± 15 m) metabolic power categories. Time in various heart rate zones was similar between standards; however peak (187±6 bpm vs. 194±5 bpm) and mean (172±7 bpm vs. 180±9 bpm) heart rate values were lower for International players. International players had greater fitness scores (YoYo IRT1-1 160±191 m vs. 781±129 m) and maximal sprint speed (27.3±0.7 vs. 26.0±1.5 km·h-1). The current findings highlight developmental gaps in match demands between standards and show that field-based fitness tests discriminate among levels of play. The external and internal loads should be used by sport organizations to assist in forming appropriate training plans and utilize the performance tests to help monitor player development.